The Impact of Prolonged Sitting and Alternate Work Positions on Musculoskeletal Discomfort and Cognitive Performance - Baker, Richelle Amanda (Curtin University, 2019)
Excessive sitting is a health issue. Some people accumulate a considerable proportion of their sitting through work. The impact of prolonged sitting and three alternative work positions on musculoskeletal discomfort and cognitive functions was investigated via laboratory studies. Results suggest sitting and alternative work positions have discomfort risks which may be clinically meaningful. Cognitive functions did not differ substantially between positions. Alternate work positions may only provide part of the solution.